Siberian tree-ring and stable isotope proxies as indicators of temperature and moisture changes after major stratospheric volcanic eruptions - O. V. Churakova (Sidorova); O. V. Churakova (Sidorova); M. V. Fonti; M. Saurer; M. Saurer; S. Guillet; C. Corona; P. Fonti; V. S. Myglan; A. V. Kirdyanov; A. V. Kirdyanov; A. V. Kirdyanov; et al. (Climate of the Past, 2019)
Stratospheric volcanic eruptions have far-reaching impacts on global climate and society. Tree rings can provide valuable climatic information on these impacts across different spatial and temporal scales. To detect temperature and hydroclimatic changes after strong stratospheric Common Era (CE) volcanic eruptions for the last 1500 years (535 CE unknown, 540 CE unknown, 1257 CE Samalas, 1640 CE Parker, 1815 CE Tambora, and 1991 CE Pinatubo), we measured and analyzed tree-ring width (TRW), maximum latewood density (MXD), cell wall thickness (CWT), and δ13C and δ18O in tree-ring cellulose chronologies of climate-sensitive larch trees from three different Siberian regions (northeastern Yakutia – YAK, eastern Taimyr – TAY, and Russian Altai – ALT). All tree-ring proxies proved to encode a significant and specific climatic signal of the growing season. Our findings suggest that TRW, MXD, and CWT show strong negative summer air temperature anomalies in 536, 541–542, and 1258–1259 at all studied regions. Based on δ13C, 536 was extremely humid at YAK, as was 537–538 in TAY. No extreme hydroclimatic anomalies occurred in Siberia after the volcanic eruptions in 1640, 1815, and 1991, except for 1817 at ALT. The signal stored in δ18O indicated significantly lower summer sunshine duration in 542 and 1258–1259 at YAK and 536 at ALT. Our results show that trees growing at YAK and ALT mainly responded the first year after the eruptions, whereas at TAY, the growth response occurred after 2 years. The fact that differences exist in climate responses to volcanic eruptions – both in space and time – underlines the added value of a multiple tree-ring proxy assessment. As such, the various indicators used clearly help to provide a more realistic picture of the impact of volcanic eruption on past climate dynamics, which is fundamental for an improved understanding of climate dynamics, but also for the validation of global climate models.